TEORI THE SPREAD OF ISNAD (Telaah Atas Pemikiran Michael Allan Cook) - Ramdhani, Imam Sahal (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2015)
erchange-newline"> It is closely related to “Common Link” phenomenon whom plenty of West Scholar on Hadith dealing their researches on it. By looking at this phenomenon, this paper is trying to review Cook’s idea about common link and the process of theory the spread of isna>d ‘s aplication in conceiving the common link phenomenon. Based on this research, we understand that Cook brought a different point of view to the Common Link phenomenon which is poured forth on his critics to the Schachtian’s theory. For Cook, there are two essential points related to Common Link. First, Common Link can’t be justifid as a hadith counterfeiter. It is because Common Link to some exctent is an engineering-work from the other narrator (periwayat). Second, Common Link can’t be a basic of hadith’s dating. Then, Cook’s point of view pulled down Commen Link theory.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />